2017
DOI: 10.1128/jcm.01939-16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation and Cost Analysis of Great Basin Shiga Toxin Direct Molecular Assay for Detection of Shiga Toxin-Producing Escherichia coli in Diarrheal Stool Specimens

Abstract: The Shiga Toxin Direct molecular assay (ST Direct) relies on nucleic acid amplification and solid array-based amplicon detection to identify Shiga toxinproducing Escherichia coli (STEC) in preserved stool specimens. Genes encoding Shiga toxin (stx 1 and stx 2 ), as well as the E. coli serotype O:157-specific marker rfbE, are simultaneously detected within 2 h. ST Direct was evaluated using 1,084 prospectively collected preserved stool specimens across five clinical centers. An additional 55 retrospectively col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…EIA has suboptimal sensitivity, particularly if a time-consuming enrichment step is not conducted 15–18. Commercial NAATs appear to be more sensitive, but results vary by study and test 19–21. NAATs are more costly than traditional microbiological techniques owing to the equipment and consumables required to perform them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EIA has suboptimal sensitivity, particularly if a time-consuming enrichment step is not conducted 15–18. Commercial NAATs appear to be more sensitive, but results vary by study and test 19–21. NAATs are more costly than traditional microbiological techniques owing to the equipment and consumables required to perform them.…”
Section: Introductionmentioning
confidence: 99%
“… 19–21 NAATs are more costly than traditional microbiological techniques owing to the equipment and consumables required to perform them. However, the higher cost may be compensated by increased ascertainment 21 and/or improved patient outcomes. 22 As laboratories consider NAATs, it is crucial to identify the best testing strategy to support time-sensitive, cost-effective treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional culture and enzyme-linked immunosorbent assay-based methods for STEC were only 33% sensitive compared with molecular testing. 50 The BioCode GI Pathogen Panel (GPP) was approved in 2018 and tests for 16 enteropathogens. While no available independent studies have been published regarding the assay's clinical utility, reported manufacturer's data suggest that both positive and negative agreements are in line with commercially available reference testing methods.…”
Section: Diagnostic Performance Of Commercially Available Food and Drug Administration-approvedmentioning
confidence: 99%